Sistem Informasi Pemasaran Perumahan Dan Pembayaran Konsumen Web - Anisa Yulia Fitri; Firdaus (Journal of Computer Scine and Information Technology, 2023)
Registration and Queuing Number at the puskesmas is one of the important factors for the community that can facilitate the process of health services and obtain more complete and efficient information. However, the registration information and queue number are still manually not using queuing tools or machines, causing long queues and patients taking too long to wait. By designing an information system, it is hoped that it can be received optimally and the development of registration and queue numbers can be planned properly. Based on these problems, it is necessary to build a system that can make it easier to overcome problems in the registration process and queue numbers, it is necessary to build a registration information system and patient queue numbers at the Padang Sibusuk Health Center web-based.